Methodological elements for the implementation of data acquisition systems as support for experimental activity in the physics teaching (2021)
RESUMEN: Experimental activity in the physics teaching can be considered as a space in which teachers create contexts for students to approach the way scientific knowledge is constructed. In this sense, the strategies for the integration of Information and Communication Technologies (ICT) in the context of science education, has a wide potential to guide experimental activity to teachers in training. Among the tools offered by ICT, Data Acquisition Systems (DAS) favor to transform the image that students have, in terms of the technical-instrumental character of this science. This paper describes the potentialities of a heuristic V diagram designed as a theoretical-methodological tool that allows to increase the potential of DAS in the physics teaching; as well as the adaptation of the Learning Model in the Physics Laboratory Works (MATLaF), is proposed with the intention of recognizing the cognitive activities that students put into play to solve experimental situations in physics.